Energy and resources cooperation for greenhouse gases emissions reduction of industrial sector. Issue 4 (June 2021) - Pyakurel, Parakram; Wright, Laurie
Energy and resources cooperation has a great potential of reducing greenhouse gases (GHG) emissions of companies, especially in industrial and business parks where facilities are located in geographical proximity. Such cooperation could cut emissions without significant impact on profit, and in some cases, may even reduce costs by decreasing waste generation and improving energy efficiency. This paper combines similar themes of industrial symbiosis, sharing economy and circular economy to formulate a single robust concept of energy and resources cooperation. A framework and methodology for mass implementation of energy and resources cooperation is proposed by integrating disparate fields of industrial ecology, business studies and industrial investments. Furthermore, an approach of enhancing such cooperation is proposed which involves an establishment of a specialized Cooperation Development and Management Company. Finally, research agenda is set out to capitalise the developments of industry 4.0 and peer to peer sharing for energy and resources cooperation.